Glorious - Benford, Gregory, 1941-; Niven, Larry (Tor, 2020)
Audacious astronauts encounter bizarre, sometimes deadly life forms, and strange, exotic, cosmic phenomena, including miniature black holes, dense fields of interstellar plasma, powerful gravity-emitters, and spectacularly massive space-based, alien-built labyrinths. Tasked with exploring this brave, new, highly dangerous world, they must also deal with their own personal triumphs and conflicts.